2014
DOI: 10.1089/zeb.2013.0920
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish: Modeling for Herpes Simplex Virus Infections

Abstract: For many years, zebrafish have been the prototypical model for studies in developmental biology. In recent years, zebrafish has emerged as a powerful model system to study infectious diseases, including viral infections. Experiments conducted with herpes simplex virus type-1 in adult zebrafish or in embryo models are encouraging as they establish proof of concept with viral-host tropism and possible screening of antiviral compounds. In addition, the presence of human homologs of viral entry receptors in zebraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 61 publications
(117 reference statements)
1
24
0
Order By: Relevance
“…3E and F). Taken together, our current findings suggest that the ZF 3-OST-6 isoform, but not 3-OST-1, -5, and -7, mediates HSV-1 entry and cell fusion in a manner similar to that of the previously reported ZF 3-OST isoforms (3-OST-2, -3, and -4) (14)(15)(16)(17). Therefore, based on the ZF 3-OST gene characterizations for HSV-1 entry, we categorize them into two groups, in which group I (3-OST-2, -3, -4, and -6) allows HSV entry, while group II (3-OST-1, -5, and -7) does not generate a gD receptor; hence, cells expressing the latter 3-OST isoforms are not susceptible to HSV-1 entry (Fig.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…3E and F). Taken together, our current findings suggest that the ZF 3-OST-6 isoform, but not 3-OST-1, -5, and -7, mediates HSV-1 entry and cell fusion in a manner similar to that of the previously reported ZF 3-OST isoforms (3-OST-2, -3, and -4) (14)(15)(16)(17). Therefore, based on the ZF 3-OST gene characterizations for HSV-1 entry, we categorize them into two groups, in which group I (3-OST-2, -3, -4, and -6) allows HSV entry, while group II (3-OST-1, -5, and -7) does not generate a gD receptor; hence, cells expressing the latter 3-OST isoforms are not susceptible to HSV-1 entry (Fig.…”
supporting
confidence: 85%
“…These ZF enzyme isoforms are differentially expressed in a tissue-specific manner, suggesting the possibility of creating a tool to study HSV tissuespecific tropism, whose study is hampered by the lack of available convenient tools. Our previous preliminary studies suggested that ZF 3-OST may mediate HSV entry (15). In this study, we investigated the ability of ZF 3-OST-1, -5, -6, and -7 isoforms, comparatively to their human analogue, to facilitate HSV-1 entry and cell-cell fusion.…”
Section: H Erpes Simplex Virus 1 (Hsv-1) Entry Into the Host Cells Rementioning
confidence: 99%
See 1 more Smart Citation
“…The first reported human pathogens that could infect and cause disease in zebrafish were bacteria (reviewed in Trede et al, 2004; van der Sar et al, 2004; Phelps and Neely, 2005; Sullivan and Kim, 2008; Meijer and Spaink, 2011; Milligan-Myhre et al, 2011; Novoa and Figueras, 2011). There are now reports of zebrafish models of human fungal (Chao et al, 2010; Brothers et al, 2011; Brothers et al, 2013; Chen et al, 2013; Gratacap et al, 2013; Kuo et al, 2013; Y.-C. Wang et al, 2013) and human viral pathogen infections (Burgos et al, 2008; Ding et al, 2011; Antoine et al, 2013; Palha et al, 2013; K. A. Gabor and C. H. Kim, personal communication). We will describe the human viral illnesses for which there are currently zebrafish infection models and then discuss the findings and insights obtained thus far from these zebrafish models of human viral infections.…”
Section: Zebrafish Models Of Human Viral Illnessesmentioning
confidence: 99%
“…HSV-1 infection has been extensively employed to elucidate STING signaling in mice (25,37). Some preliminary studies suggested that HSV-1 could potentially infect zebrafish and persist in adult zebrafish brain (13,38). It remains unknown whether HSV-1 infection could be adapted to explore cytosolic DNA signaling in zebrafish.…”
mentioning
confidence: 99%